New methods to image transcription in living fly embryos: the insights so far, and the prospects. (19th February 2016) - Ferraro, Teresa; Lucas, Tanguy; Clémot, Marie; De Las Heras Chanes, Jose; Desponds, Jonathan; Coppey, Mathieu; Walczak, Aleksandra M.; Dostatni, Nathalie
Abstract : The regulation of transcription is a fundamental process underlying the determination of cell identity and its maintenance during development. In the last decades, most of the transcription factors, which have to be expressed at the right place and at the right time for the proper development of the fly embryo, have been identified. However, mostly because of the lack of methods to visualize transcription as the embryo develops, their coordinated spatiotemporal dynamics remains largely unexplored. Efforts have been made to decipher the transcription process with single molecule resolution at the single cell level. Recently, the fluorescent labeling of nascent RNA in developing fly embryos allowed the direct visualization of ongoing transcription at single loci within each nucleus. Together with powerful imaging and quantitative data analysis, these new methods provide unprecedented insights into the temporal dynamics of the transcription process and its intrinsic noise. Focusing on the Drosophila embryo, we discuss how the detection of single RNA molecules enhanced our comprehension of the transcription process and we outline the potential next steps made possible by these new imaging tools. In combination with genetics and theoretical analysis, these new imaging methods will aid the search for the mechanisms responsible for the robustness of development. WIREs Dev Biol 2016, 5:296–310. doi: 10.1002/wdev.221 This article is categorized under: Gene Expression and Transcriptional Hierarchies > Regulatory Mechanisms Gene Expression and Transcriptional Hierarchies > Quantitative Methods and Models